Training load and intensity distribution for sprinting among world-class track cyclists - Desgorces, F.-D.; Slawinski, J.; Bertucci, W.; Rousseau, F.; Toussaint, J.-F.; Noirez, P. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Only few studies analyzed real training programs of sprinters while that should be a valuable step in the understanding of sprint training. The present study aimed at characterizing track cycling sprinter training by training load and intensity distribution. METHODS: Twenty-nine weeks of prechampionship training data were retrospectively analyzed for 6 world-class athletes. Training load was measured by the ratio of volume completed to maximal volume and categorized by five intensity zones (endurance: zones1-2; sprinting: zones3-5) and exercise type (on-bike or resistance). Intra-week (training monotony) and inter-week (acute-chronic workload ratio) variation was also studied. RESULTS: On-bike training represented 77.4±15.3% of total training load; resistance training, 22.6±15.2% (note high standard deviation). Total weekly training load significantly varied (P=0.0002) with high acute-chronic workload ratio (12.0±3.2 weeks >1.5 or <0.8), but low intra-week variations (training monotony, 1.81±0.20). Zone4 and zone5 made up 74.4±16.9% of total training load; zone1, 15.8±11%. Training load was seldom in zone2 (6.4±5.3%) or zone3 (3.3±4.2%). From the first to the second half of the period, zone3-4 training load decreased (39.3±3.3 to 27.4±1.7%; P=0.01), while zone5 increased (34.9±2.4 to 50±3.7%; P=0.002). CONCLUSIONS: In this reduced group of elite athletes, training appeared to mainly consist of on-bike exercises within the highest intensity zones. As demonstrated by monotony and acute-chronic workload ratio overloading and unloading are based on high variations over weeks, not days. Essentially, this study describes a polarized intensity distribution on the highest intensities which increased with world championships approach.